The Intuitive-Override Model: Nudging Judges Toward Pretrial Risk Assessment Instruments. - DeMichele, Matthew; Comfort, Megan; Barrick, Kelle; Baumgartner, Peter (Federal Probation, 2021)
HOW DO JUDGES make pretrial releasedecisions? Unsurprisingly, judges' perceptions of theutility of the risk assessment instrument werestrongly shaped by the overlap between theinformation they considered valuable whenexercising their decision-making and theinformation used to complete the risk assessment. Although we did not assessthe changes in prediction errors when usingthe instrument, another judge described herdesire to understand the nature of the researchby stating that it would be helpful to see probabilitiesof positive outcomes: It would not be helpful for judges to seeactual probabilities of people for an FTAor a new crime. Judicial Decision Making Nearly 90 years ago, the legal scholar JeromeFrank (1930) observed that judges basetheir decisions on hunches, and "whateverproduces judges' hunches makes the law."Frank recognized the importance of judicialsubjectivity and intuition when making decisions.